CHARLES BENETTO’S DREAM IN DEPRESSIVE CONDITION AND ITS EFFECT DEPICTED IN MITCH ALBOM’S FOR ONE MORE DAY - ULFA, DIAN SOPHIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Depression, Jungian Dream, Personality, For One More Day. For One More Day by Mitch Albom portrays a psychological condition of human being. It is one of the novels that explores that issue, especially regarding dreaming in depressive condition and personality changes. These things can be identified through the character, named Charles Benetto, as the representation of human in the reality. Therefore, the objectives of this study are: (1) to explore the relation between Charles’ depression and his dream (2) to discover how Charles’ dream changes his personality.This study is carried out using qualitative approach since the psychological phenomenon of the main character is analyzed in descriptive ways. Jungian dream and personality theories are applied in analyzing the data that are found in the novel. Charles, the main character of the novel, has several symptoms as depressed person after facing several problems in his life that happen within his family. The causes and desires regarding his depression remain in his unconscious. Those affect his mind and later appear in his dream. He dreams about things that worry him and wishes that are unfulfilled. This dream gives a great influence on Charles’ personality in the future since in the dream he gets several life lessons through the conversation with his deceased mother and expectation that is finally met. In conclusion, there is a relation between Charles’ depression and his dream, and his dream affect the change of Charles’ personality in the future.Hopefully, the next researchers can analyze more about how Charles personality develops since childhood to adolescence and as a divorced child. Things about divorcement that is portrayed in the novel can also be explored more.